THE PERMO-TRIASSIC TRANSITION IN SPITSBERGEN: δ13C ORG CHEMOSTRATIGRAPHY, FE AND S GEOCHEMISTRY, FACIES, FAUNA AND TRACE FOSSILS - Wignall P.B.; Morante R. (My University, 1998)
New δ13C org analyses of two boundary sections between the late Permian Kapp Starostin Formation and the early Triassic Vardebukta Formation of western Spitsbergen confirm field evidence that their contact is a conformable one. Thus, contrary to previous reports, some Spitsbergen sections contain a complete record of the environmental and faunal changes during the crisis interval of the end Permian mass extinction. No environmental deterioration is recorded in the late Permian until near the end of the terminal Changxingian Stage, whereupon the abundant siliceous sponge fauna of the Kapp Starostin Formation disappears along with the deep-burrowing fauna responsible for the Zoophycus trace fossil. A low diversity dysaerobic trace fossil assemblage is briefly developed before a transition to finely laminated, pyritic facies immediately beneath the Permo-Triassic boundary. Analysis of the S/C ratios from the laminated strata suggests that free H2S was present in the water column (euxinic conditions) even in relatively nearshore settings subject to storm sandstone deposition. The mass extinction crisis in Spitsbergen is therefore coincident with the extensive development of oxygen-poor conditions in the water column and compares closely, both in timing and nature, with the crisis seen in lower latitude Tethyan settings. However, the subsequent aftermath and recovery in the Boreal sections of Spitsbergen was more rapid than in Tethys. Thus, a shoreface sandstone body within the Dienerian Stage contains an appreciable diversity of fauna (by the standards of the early Triassic), including bryozoans, calcareous algae and deep infaunal bivalves, that suggests the marine ecosystem recovery began earliest in higher palaeolatitudes.
Keywords: Triassic; Mesozoic::Triassic; Мезозой::Триасовая